Alternative Precursors for the Synthesis of Binary Sb2E3 and Bi2E3 (E = S, Se, Te) Nanoparticles by the Hot Injection Method. Issue 22 (4th July 2016) - Rusek, Monika; Bendt, Georg; Wölper, Christoph; Schulz, Stephan
Abstract : Intramolecularly stabilized Sb(OCH2 CH2 NMe2 )3 (1 ) and Bi(OCH2 CH2 NMe2 )3 (2 ) readily react with (Me3 Si)2 S and (Et3 Si)2 E (E = Se, Te) at moderate temperatures (hot injection method) with elimination of the corresponding silyl ether and subsequent formation of the group 15 chalcogenides Sb2 E3 and Bi2 E3, which were characterized by XRD, SEM, and energy‐dispersive X‐ray spectroscopy (EDX). In addition, the solid‐state structure of1 was determined by single‐crystal XRD. Abstract : Binary antimony (Sb2 E3 ) and bismuth chalcogenide (Bi2 E3 ) nanoparticles were obtained by reaction of Sb(OCH2 CH2 NMe2 )3 and Bi(OCH2 CH2 NMe2 )3 with (R3 Si)2 E (E = S, Se, Te; R = Me, Et) at moderate temperatures. The reactions were studied by in situ 1 H NMR spectroscopy, and the products were characterized by energy‐dispersive X‐ray spectroscopy, XRD, IR spectroscopy, and SEM.